Studying the activity of microorganisms (laboratory conditions) in moderately and highly saline meadow alluvial soils based on cotton - Tog`ayeva, Muhayyo (Центр Научных Публикаций (buxdu.uz), 2023)
In the article, an experiment was carried out on the irrigated soil of the "Central Asia" farm, Bukhara region, Bukhara district, with moderate salinity, and some places with strong salinity. The composition of the biofertilizer used in the experiment consisted of micro and macrogreen algae and high plant residues. Including organic substances 50-60%, humus 22-27%, nitrogen 10-12%, phosphorus 5-7%, potassium 1.8-2.1%, albumen 35-40%, 17 amino acids and copper, zinc and other from trace elements are available. Experiments have been carried out in three options when the macerated microalgae suspension is planted and mineral fertilizer (NPK No.) is added and the number of ammonifiers is increased from 1,900,000 to 1,200,000, fungi from the first 8 thousand to 12 thousand; it was found that the number of green microorganisms increased from 200,000 to 950,000.